Redesign sepatu Mary Jane untuk wanita dengan konsep estetika Coquette berbasis Metode MFC - Nurhidayat, Martiyadi; Khalisha, Alma Femira; Syarif, Edwin Buyung (Institut Seni Indonesia Yogyakarta, 2025)
As postmodern aesthetics develop in the digital world, the coquette trend is becoming increasingly popular, especially among Gen-Z. One fashion product that can be associated with this aesthetic is the Mary Jane model shoe, which has long been known for its classic and feminine design. This study uses the Morphological Forced Connection (MFC) method to explore various design alternatives that adapt the coquette aesthetic elements of Mary Jane shoes. Data were obtained through literature studies, market observations, and questionnaires involving women aged 18–26 years to understand user preferences. The results of the exploration using the MFC method produced 243 design combinations, which were then narrowed down to three main alternatives. The final design chosen based on aesthetic analysis and user preferences, resulted in